LANGUAGE DISCORD AND LANGUAGE ATTITUDE AMONG EFL LEARNERS: INSIGHTS FROM AN INDONESIAN UNIVERSITY - Nashruddin, Nashruddin; Setiawan, Slamet; Suhartono, Suhartono (LLT Journal: A Journal on Language and Language Teaching, 2024)
Language discord is one of problems experienced by Indonesian EFL learners when producing English utterances, and those problems can affect their language attitude towards English. The objectives of this research are to find (1) forms of language discord experienced by EFL learners when producing English utterances, (2) factors causing the language discord, and (3) language attitudes towards English as the effect of the language discord. Employing a qualitative approach, this case study was conducted at a university in South Sulawesi, and purposive sampling technique was used to obtain research participants. Based on certain criteria regarding the samples that were most suitable and considered to produce the desired data, four students from the English education department were selected as research participants. Data collection involved observations and in-depth interviews. The technique of data analysis involved a procedure consisting of data managing, reading and giving a memo, describing, classifying, data interpretation, visualizing, and representing. Findings showed three forms of language discord: naked language discord, disguised language discord, and uncontrolled language discord. From the interview results, three factors that caused language discord were found: high excitement, unpreparedness, and deference. As the effect of the language discord, the EFL learners stated they were more enthusiastic to become proficient English speakers, and they felt trained to memorize English vocabularies.